Optimalisasi Asupan Cairan dengan Tekanan Darah dan Denyut Nadi pada Atlet PS Sleman Development Center - Yuni Afriani; Siska Sari; Adi Sucipto; Desty Puspaningtyas (Universitas Mathla'ul Anwar Banten, 2022)
Physical exercise is an important key to support athlete's success. Optimal nutritional intake is needed to support the performance. Dehydration cases in teenage soccer athletes are high. Inappropriate fluid intake, both in type and amount, has an effect on blood pressure and heart rate instability. It is necessary to identify factors that can affect blood pressure and heart rate instability in athletes based on fluid intake. Fluid intake data is measured by the SQFFQ (Semi Quantitative Food Frequency Questionnaire) Fluids questionnaire. The data was statistically analyzed using the Krusikal Wallis test. Blood pressure and heart rate data using digital tensimeter. As many as 96% of athletes at PS Sleman Development Center have not consumed fluids as needed. The average fluid intake of soccer athletes was 2,797.61 ± 1,100.64 ml. The average systolic blood pressure of athletes was 118.25 mmHg, diastolic pressure was 73.67 mmHg, and heart rate was 72.78 times/minute. There was a significant association in energy drink intake with changes in heart rate (p<0.05), but no significantly difference in systolic and diastolic blood pressure (p>0.05). The fluid intake of athletes was still relatively lacking and has not matched the volume, type, and period of training.